LO14: Unrecognized delirium in a cohort of older ED patients assessed at a tertiary care center: signs of improvement?. (May 2019) - Lee, J.; Tong, T.; Tierney, M.; Kiss, A.; Chignell, M.
Abstract : Introduction : BACKGROUND: Recognition rates of delirium in older ED patients were reported between 13 to 25% in studies conducted in the U.S in the 1990's. Recently, there has been increased attention to delirium in Emergency Medicine, with the development of Geriatric curriculums in Canada specifically focused on delirium. However rates of delirium recognition have not been reassessed in Canadian ED's. OBJECTIVES: To assess the rate of delirium recognition by ED staff in a cohort of older ED patients assessed at a tertiary care Canadian ED.Methods : STUDY DESIGN: Prospective observational cohort study at a Canadian teaching ED. PARTICIPANTS: Eligible patients were aged ≥70 years and older who had stayed in the ED for a minimum of 4 hours. We excluded patients who were critically ill, visually impaired or otherwise unable to communicate. DATA COLLECTION: Trained research assistants approached clinical staff prior to approaching patients to confirm that patients were delirium free. They then assessed demographics, ED length of stay (LOS) and cognition using the validated Montreal Cognitive Assessment scale (MOCA), mini-mental status exam (MMSE), delirium index and Richardson Agitation Scale (RASS) at baseline. Delirium was assessed using the validated Confusion Assessment Method (CAM). We report descriptive statistics and 95% confidence intervals (CI) where appropriate.Results : We enrolled 203 patients of which 102 (50.3%) were female. Their mean age was 81.0 years, mean LOS was 16.3 hours, mean MOCA was 23.4 and mean MMSE was 26.7. RA's detected delirium using the CAM in 16/203 patients (7.9%, 95% CI 4.6 to 12.5%). Mean MOCA and MMSE for delirious patients was 13.4 and 18.3 and their mean DI was 6.4. All CAM positive patients were deemed to be delirium free by clinical staff. RA alerted clinical staff in all cases where patients had delirium, but 3/16 were discharged home (18.8%, 95% CI 4.1 to 45.7%).Conclusion : Our findings confirm previous low delirium recognition rates in a Canadian Tertiary ED. Future research should explore barriers and facilitators to recognizing delirium in the ED.